Psychological Anxiety of College Students' Foreign Language Learning in Online Course - Wang, Xue; Zhang, Wei (Frontiers in Psychology, 2021)
Anxiety is one of the most important affective factors affecting college students' foreign language learning. Especially in the Internet age, new teaching ideas and methods bring new load and anxiety to students' psychology. Taking students who attend a college English online course learning as the research object, this paper analyzes the general situation and professional skills of the students' psychological anxiety under the network environment by using the method of investigation and data analysis. It conceives six methods to reduce the students' psychological anxiety according to the reason analysis and summarizes the more effective ways with data mining of another questionnaire. It points out that teachers can advocate the mode of group learning and peer cooperation, strengthen the timeliness and diversity of tests, increase the richness of extracurricular activities, and increase teachers' and students' quality of online teaching and learning to reduce the anxiety of students' foreign language learning in an online teaching environment.